The Impact of Natural Culture and Economic Ideology on Managerial Work Values: A Study of the United States, Russia, Japan, and China - Ralston, David A.; Holt, David H.; Terpstra, Robert H.; Kai-cheng, Yu (Journal of International Business Studies, 1997)
This study assesses the impact of economic ideology and national culture on the individual work values of managers in the United States, Russia, Japan, and China. The convergence-divergence-crossvergence (CDC) framework was used as theoretical framework for the study, while the Schwartz Value Survey (SVS) was used to operationalize over investigation of managerial work values across these four countries. The findings largely support the crossvergence prospective, while also confirming the role of national culture. Implications from the findings are drawn for the convergence-divergence-crossvergence of values, as well as for the feasibility of multidomestic or global strategies for a corporate culture.